Spray-assisted layer-by-layer assembly on hyaluronic acid scaffolds for skin tissue engineering - Monteiro, I. P. (2015)
Tissue engineering approaches for the development of a single epidermal-dermal scaffold to treat full-thickness skin defects have been limited by difficulties in the fabrication of a bilayer scaffold combining the specific properties of the epidermis and the dermis. Here we present an innovative approach to developing a scaffold that holds promise for skin tissue engineering. We utilize the spray-assisted layer-by-layer assembly technique to deposit a polyelectrolyte multilayer film composed of hyaluronic acid and poly-L-lysine (the epidermal component) on a porous hyaluronic acid scaffold (the dermal component), in a rapid and controlled manner. The multilayer film promotes cell adhesion, contributing to regeneration of the epidermal barrier functions of skin. While human keratinocytes attached and proliferated on the coated porous scaffolds, they did not invade the porous dermal component, thus leaving room for seeding of relevant fibroblast cell types in this scaffold. This scaffold therefore holds promise for co-culture of different cells, which may be useful for treatment of full-thickness skin defects as well as other tissue engineering applications.